Evaluation of Intestinal Permeability and Liver Bacterial Translocation in Two Modern Broilers and Their Jungle Fowl Ancestor - Baxter, Mikayla F. A.; Dridi, Sami; Koltes, Dawn A.; Latorre, Juan D.; Bottje, Walter G.; Greene, Elizabeth S.; Bickler, Stephen W.; Kim, Jae H.; Merino-Guzman, Ruben; Hernandez-Velasco, Xochitl; Anthony, Nicholas B.; Hargis, Billy M.; et al. (Frontiers in Genetics, 2019)
The objective of this study was to evaluate the of intestinal permeability and liver bacterial translocation (BT) across a modern commercial broiler, a commercial broiler of 1995 genetics, and an unselected Jungle Fowl line. Modern 2015 (MB2015) broiler chicken, random bred line initiated from 1995 (RB1995), and the Giant Jungle fowl (JF). Chickens were randomly allocated to four different dietary treatments. Dietary treatments were (1) a control corn-based diet throughout the trial [corn-corn (C-C)]; (2) an early phase malnutrition diet where chicks received a rye-based diet for 10 days, and then switched to the control diet [rye-corn (R-C)]; (3) a malnutrition rye-diet that was fed throughout the trial [rye-rye (R-R)]; and (4) a late phase malnutrition diet where chicks received the control diet for 10 days, and then switched to the rye diet for the last phase [corn-rye (C-R)]. Paracellular permeability was evaluated using fluorescein isothiocyanate dextran (FITC-D). Liver BT was also evaluated. MB2015 and RB1995 consuming the rye-based diet showed increase serum levels of FITC-D when compared to the corn-fed chickens (P < 0.05). Overall, MB2015 appeared to have higher enteric permeability than the JF. To our knowledge, this would be the first paper to evaluate the effect of compensatory growth on intestinal permeability and liver BT. Further studies to evaluate microbiome and inflammatory markers in these chicken models are currently being evaluated.